O PROGRAMA DE MESTRADO EM CONTABILIDADE DA UERJ - Fernandes, Antônio Miguel; Valadares, Eduardo Bernardo Monteiro; Arieira, Osiane Nascimento; Aragão, Rodrigo Barros; Machado, Gilcina Guimarães (Revista de Contabilidade do Mestrado em Ciências Contábeis da UERJ, 2013)
Vide artigo.